This preview shows page 1. Sign up to view the full content.
Unformatted text preview: sier to solve this by factoring. However, we are going to
use the quadratic formula anyway to make a couple of points.
First, let’s rearrange the order a little bit just to make it look more like the standard form. - x 2 + 16 x = 0
Here are the constants for use in the quadratic formula. a = -1 b = 16 c=0 There are two things to note about these values. First, we’ve got a negative a for the first time.
Not a big deal, but it is the first time we’ve seen one. Secondly, and more importantly, one of the
values is zero. This is fine. It will happen on occasion and in fact, having one of the values zero
will make the work much simpler.
Here is the quadratic formula for this equation. x= -16 ± (16 ) - 4 ( -1)( 0 )
2 ( -1)
2 -16 ± 256
-16 ± 16
-2 = Reducing these to integers/fractions gives, x= -16 + 16 0
2 x= -16 - 16 -32
-2 So we get the two solutions, x = 0 and x = 16 . These are exactly the solutions we would have
gotten by factoring the equation.
[Return to Problems] © 2007 Paul Dawkins 101 http://tutorial.math.lamar.edu/terms.aspx College Algebra To this point in both this section and the...
View Full Document
- Spring '12